Doing Action Research in Your Own Organization - Coghlan, David (SAGE Publications, Ltd. (UK), 2019)
Concise and unintimidating, the fifth edition of this bestselling book is the only pragmatic, quick-start guide to the main theories, issues, and approaches to insider action research. With an encouraging and approachable tone, David is the perfect mentor for anyone conducting action research in their own organization. Calming nerves at the same time as building confidence, he helps readers devise an appropriate research design that anticipates possible challenges and fits within the limits of their environments. A complete do-it-yourself toolkit for every step of the action research process, this edition is outfitted with: Real-world student and professional case studies Author video tips Annotated templates Progress checklists Journal articles, weblinks, and other further reading. To the point without losing clarity or thoroughness, this book is the hands-on manual for all the need-to-know facts about understanding and undertaking insider action research.